Improving the organic solvent resistance of lipase a from Bacillus subtilis in water–ethanol solvent through rational surface engineering. (October 2021) - Min, Kyoungseon; Kim, Hee Taek; Park, Si Jae; Lee, Siseon; Jung, Ye Jean; Lee, Jin-Suk; Yoo, Young Je; Joo, Jeong Chan
Graphical abstract: Highlights: Engineering of ethanol-interacting sites of lipase A for improving stability. The Ser16Gly mutant showed 1.8-fold higher stability than wild-type in 50% ethanol. The Leu108Asn mutant showed 1.5-fold higher thermostability than wild-type at 45 °C. This strategy can be applicable for constructing organic solvent-resistant enzymes. Abstract: Given that lipase is an enzyme applicable in various industrial fields and water-miscible organic solvents are important reaction media for developing industrial-scale biocatalysis, a structure-based strategy was explored to stabilize lipase A from Bacillus subtilis in a water–ethanol cosolvent. Site-directed mutagenesis of ethanol-interacting sites resulted in 4 mutants, i.e., Ser16Gly, Ala38Gly, Ala38Thr, and Leu108Asn, which were stable in 50% ethanol and had up to 1.8-fold higher stability than the wild-type. In addition, Leu108Asn was more thermostable at 45 °C than the wild type. The results discussed in this study not only provide insights into strategies for enzyme engineering to improve organic solvent resistance but also suggest perspectives on pioneering routes for constructing enzyme-based biorefineries to produce value-added fuels and chemicals.